Pengaruh Program Magang, Minat Kerja, dan Keputusan Karir, Terhadap Kesiapan Kerja Mahasiswa Manajemen Tahun 2021 - Aisyah, Siti; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of internship programs, job interests, and career decisions on the work readiness of Management students in 2021. The research method used is quantitative with multiple regression analysis. The data obtained were processed using IBM SPSS statistics version 21. This study uses a quantitative approach using primary data through the distribution of online questionnaires via Google Form to management students at Nahdlatul Ulama University, West Kalimantan. The sample in this study was 43 respondents with a sampling technique using purposive sampling with Likert scale measurements. The results of this study indicate that the variables of internship programs, job interests, and career decisions simultaneously have a significant effect on student work readiness. The internship program variable (X1) has a t-value of 2.501> 2.024 and a sig value for the internship program of 0.017 < 0.05. The work interest variable (X2) has a t-value of 2.754> 2.024 and a sig value for work interest of 0.009 < 0.05. The career decision variable (X3) has a t-value of 3.383 > 2.024 and a sig value for career decisions of 0.002 < 0.05. The regression equation obtained is Y = 1.737 + 0.217 + 0.243 + 0.241 with a coefficient of determination (R²) of 43.8%. This means that Work Readiness is influenced by 43.8% by internship programs, job interests, and career decisions, while the rest is influenced by other factors not studied.